Introduction to the macroeconomic dynamics: Special issues on money, credit, and liquidity - Ed Nosal; Christopher Waller; Randall Wright (Federal Reserve Bank of Chicago, 2010)
We motivate and provide an overview to New Monetarist Economics. We then briefly describe the individual contributions to the Macroeconomics Dynamics special issues on money, credit and liquidity.
Keywords: 330; Monetarismus; Finanzmarkt; Kredit; Gesamtwirtschaftliche Liquidität; Börsenkurs; Bank